1998
DOI: 10.1002/chin.199838268
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: A Heteroaromatic Acid from Marine Sponge Suberites vestigium.

Abstract: A Heteroaromatic Acid from Marine Sponge Suberites vestigium.-Compound (I) is isolated from the butanol fraction of the marine sponge Suberites vestigium. It is the first time that a pyrazole derivative is isolated from marine flora and fauna. -(MISHRA, P. D.; WAHIDULLAH, S.; KAMAT, S. Y.; Indian J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Pyrazoles are important compounds that have many derivatives with a wide range of interesting properties [1][2][3][4]. Recyclization reactions of 4-benzoyl-5-phenyl-2,3-dihydro-2,3-furandione with various phenylhydrazones and phenylhydrazine lead to pyrazolecarboxylic acid and pyridazinones [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazoles are important compounds that have many derivatives with a wide range of interesting properties [1][2][3][4]. Recyclization reactions of 4-benzoyl-5-phenyl-2,3-dihydro-2,3-furandione with various phenylhydrazones and phenylhydrazine lead to pyrazolecarboxylic acid and pyridazinones [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazole, five‐member heterocyclic ring with two adjacent nitrogen atoms, has gained a great attention in pharmaceutical and chemical industries . A large number of pyrazoles showed various biological activities such as anticancer, antihistaminic, pesticidal, antifungal, anti‐rheumatoid arthritis, anticonvulsant, antidepressant, antipyretic, antibacterial, antituberculosis, antiviral, and anti‐inflammatory activities.…”
Section: Introductionmentioning
confidence: 99%
“…For example, water molecules at protein-DNA interface contribute to the complex formation and potentially play important role in mediating specific interactions [16][17][18]. The chemistry of pyrazole derivatives has been the subject of research due to their importance in various applications and their wide spread of potential biological and pharmacological activities governed by specific interactions between host and receptors [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. In the present study, self assembly of compound (2) mediated through water molecules is reported which reveals an CAHÁ Á ÁO contact between 0022-2860/$ -see front matter Ó 2011 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%